2016
DOI: 10.1371/journal.pone.0165784
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Genotyping of Coxiella-Like Endosymbionts in Ticks that Infest Horses in South Korea

Abstract: Members of the genus Coxiella can be transmitted from ticks to humans during contact with animals; Coxiella may thus spread from the infected horses or ticks to humans. In this study, the presence of Coxiella burnetii and Coxiella-like endosymbionts (CLE) in ticks found on infested horses was determined using PCR and genotyping. A total of 213 ticks were randomly collected from 51 horses (4–5 ticks per horse) raised on Jeju Island, Korea, between 2009 and 2013. All ticks were morphologically identified as adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
3
26
1
Order By: Relevance
“…I. persulcatus, D. nuttalli, H. asiaticum, D. marginatus, and D. niveus are the dominant tick species in Xinjiang [38], and their wide distribution has a significant impact on the development of animal husbandry and public health. rufipes, H. anatolicum, or H. punctata, the findings lead us to suspect that C. burnetii has these relationships in these ticks, particularly because some reports have shown that C. burnetii has a high infection rate and vertical transmission relationship among some ticks [41][42][43][44]. Confirmation of our hypothesis requires more literature support and research to prove; here we are merely stating the supposition.…”
Section: Discussionmentioning
confidence: 61%
“…I. persulcatus, D. nuttalli, H. asiaticum, D. marginatus, and D. niveus are the dominant tick species in Xinjiang [38], and their wide distribution has a significant impact on the development of animal husbandry and public health. rufipes, H. anatolicum, or H. punctata, the findings lead us to suspect that C. burnetii has these relationships in these ticks, particularly because some reports have shown that C. burnetii has a high infection rate and vertical transmission relationship among some ticks [41][42][43][44]. Confirmation of our hypothesis requires more literature support and research to prove; here we are merely stating the supposition.…”
Section: Discussionmentioning
confidence: 61%
“…And there are 14 T. equi-transmissible tick species, which are 4 Dermacentor spp., 4 Hyalomma spp., 5Rhipicephalus spp., and Amblyomma cajennense (Wise et al, 2013). In Korea, the predominant horse tick species isHaemaphysalis longicornis (Seo et al, 2016). To date, EP-transmissible tick species have not been found in ROK (Jiang et al, 2019;Yun et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The high infection rate of C. burnetii in D. silvarum, H. asiaticum, and R. sanguineus seems to be related to the symbiosis and vertical transmission between them [41,42]. Although there is no related article reporting the existence of symbiotic and vertical anatolicum, or H. punctata, the findings lead us to suspect that C. burnetii has these relationships to these ticks, particularly because some reports have shown that C. burnetii has a high infection rate and vertical transmission relationship among some ticks [43][44][45][46]. Confirmation of our hypothesis requires more literature support and research to prove; here we are merely stating the supposition.…”
Section: Discussionmentioning
confidence: 96%